Development of Vocational Curriculum at SMK Wicaksana Al-Hikmah II Benda Brebes Regency - Naufary, Alfiyan (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2024)
This study aims to analyze and develop a vocational curriculum at SMK Wicaksana Al-Hikmah II Benda, Brebes Regency, in order to improve the relevance of vocational education to the needs of the workforce. This research approach uses a qualitative descriptive method with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the vocational curriculum implemented still requires strengthening in terms of synchronization with local and national industry needs. The curriculum development process is carried out through needs analysis, adjustment of core competencies, and integration of project-based learning. The implementation of this new curriculum is designed to equip students with technical and non-technical skills, such as communication skills, teamwork, and problem solving. Thus, the development of this vocational curriculum is expected to improve the competence of vocational school graduates so that they are better prepared to compete in the workforce and are able to meet industry demands.